Parametric Analysis of Open-ended Waveguide Array Feeder for Cosecant-Squared And Pencil Beam Radiation Pattern - Yucedag, Okan Mert; Senturk, Mustafa Dagcan; Turk, Ahmet Serdar (IEEE, 2012)
This paper deals with the parametric analysis of an open-ended waveguide array, which is used as feeder for parabolic reflector antennas. The main aim of the study is to obtain desired radiation characteristics for air and coastal surveillance radars such as, pencil beam, suppressed side lobes, electronic beam scanning and cosecant-squared pattern shapes. The analytical regularization method is used a fast and accurate way to solve the problem of E-polarized wave diffraction by perfectly electrical conductive (PEC) waveguide array combined with a modified reflector for basic stage of antenna design process. The numerical procedure is initially verified by the analytical methods and the calculated results are presented for the proposed designs.
Keywords: Open-ended waveguide array; Reflector antenna; Cosecant-squared pattern; Analytical regularization method; DIFFRACTION; Engineering; Telecommunications